Vocal individuality of in-air Weddell seal (Leptonychotes weddellii) pup 'primary' calls - K Collins; J Terhune; T Rogers; K Wheatley; R Harcourt (2006)
As a result of selective pressures faced during lactation, vocal recognition may play a crucial role in maintaining the phocid mother–pup bond during the period of dependence. To investigate this possibility, we examined whether Weddell seal (Leptonychotes weddellii) pups produce individually distinctive “primary” calls. One temporal, nine fundamental frequency features, and two spectral characteristics were measured. A discriminant function analysis (DFA) of 15 Vestfold Hills pups correctly classified 52% of calls, while the cross-validation procedure classified 29% of calls to the correct pup. A second DFA of 10 known-age McMurdo Sound pups correctly classified 44% of “test” calls. For novel calls, the probabilities of attaining such classification rates by chance are low. The relationship between age and call stereotypy indicated that pups 2 wk and older may be more vocally distinctive. Overall, findings suggest that Weddell seal pup “primary” calls are moderately distinctive and only exhibit sufficient stereotypy to aid maternal recognition by approximately two weeks of age.